2009
DOI: 10.1002/cplx.20269
|View full text |Cite
|
Sign up to set email alerts
|

Are complex systems hard to evolve?

Abstract: Evolutionary complexity is measured here by the number of trials/evaluations needed for evolving a logical gate in a nonlinear medium. Behavioral complexity of the gates evolved is characterized in terms of cellular automata behavior. We speculate that hierarchies of behavioral and evolutionary complexities are isomorphic up to some degree, subject to substrate specificity of evolution, and the spectrum of evolution parameters.2009 Wiley Periodicals, Inc. Complexity 14: 15-20, 2009 Key Words: logic gates; e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…• Gates in cellular automata [37]: OR NOR AND NAND XOR • Gates in Physarum: AND OR NAND NOR XOR XNOR We see that in all systems quoted the gate XOR is the most difficult to find, develop or evolve. Why is it so?…”
Section: Discussionmentioning
confidence: 99%
“…• Gates in cellular automata [37]: OR NOR AND NAND XOR • Gates in Physarum: AND OR NAND NOR XOR XNOR We see that in all systems quoted the gate XOR is the most difficult to find, develop or evolve. Why is it so?…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, s Figure 11 illustrates three different kinds of dynamics emerging in ECAM rule 126, for some values of τ . 5 Exploring different values of τ , we found that large odd values of τ tend to define macrocells-like patterns [Wolfram, 1994], [McIntosh, 2009], while even values are responsible for a mixture of periodic and chaotic dynamics. Figure 11(a)i illustrates large periodic regions with few complex patterns traveling isolation developed by function φ R126min:3 .…”
Section: Filters Help For Discover Hidden Dynamicsmentioning
confidence: 99%
“…Complexity of a system is almost never quantified but often related to unpredictability. Theory of cellular automata (CA) refers to complexity its entire life [von Neumann, 1966], [Adamatzky & Bull, 2009], [Boccara, 2004], [Chopard & Droz, 1998], [Hoekstra et al, 2010], [Kauffman, 1993], [Margenstern, 2007], [McIntosh, 2009], [Mainzer & Chua, 2012], [Mitchell, 2002], [Morita, 1998], [Margolus et al, 1986], [Poundstone, 1985], [Park et al, 1986], [Toffoli & Margolus, 1987], [Schiff, 2008], [Sipper, 1997], [Wolfram, 1986], [Martínez et al, 2013a], [Martínez et al, 2013b]. Due to transparency of cellular automata structures their complexity can be measured and analysed [Wolfram, 1984a], [Culik II & Yu, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, s of τ . 2 Exploring different values of τ , we found that large odd values of τ tend to define macrocellslike patterns [40,26], while even values are responsible for a mixture of periodic and chaotic dynamics. Figure 4(a) illustrates large periodic regions with few complex patterns travelling isolation developed by function φ R126min:3 .…”
Section: Dynamics Emerging In Eca Rule 126 With Memorymentioning
confidence: 99%
“…Complexity of a system is almost never quantified but often related to unpredictability. Theory of cellular automata (CA) deal with complexity its entire life [34,2,11,12,14,26,28,39,22]. Due to the transparency of CA structures, their complexity can be measured and analyzed [38,13].…”
Section: Introductionmentioning
confidence: 99%